Fenomena Pengajian Berbayar Ustad Hanan Attaki - Wibawa, Agung Tirta; Sarbini, Ahmad; Rusliana , Iu (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to understand the phenomenon of paid religious gatherings (pengajian) in hotels, which adopt a "sharing time" concept, particularly regarding the interest of younger audiences who prefer these events over traditional gatherings held in mosques or prayer halls. Utilizing the concept of religious commercialization, this research examines lifestyle changes and the socio-cultural impacts brought about by this practice. The commercialization of religion, which commodifies religious activities, manifests in the form of paid religious gatherings in hotels, creating new dynamics in the relationship between religion and society. The study also highlights the role of social media in the popularity of religious figures, such as Ustad Hanan Attaki, who leverage digital platforms to build personal branding and attract the attention of younger generations. This trend illustrates how modernization, urbanization, and social media influence society's interaction with religion. Additionally, the theory of religious consumption explains that paid religious gatherings are part of the modern lifestyle that emphasizes comfort and exclusivity. The study concludes that the phenomenon of paid religious gatherings in hotels not only reflects the commodification of religion but also serves as a status symbol among the urban middle class. Religious gatherings, which were originally egalitarian in nature, have now transformed into exclusive spaces, signaling a shift in religious values from spirituality towards consumption and social status.Through various theoretical approaches, this research demonstrates that paid religious gatherings in hotels reflect transformations in religious practices and social interactions, representing the challenges modernity poses to traditional values. Keywords: Religious Gathering; Paid; Hanan Attaki